(untitled) (Filološke studije, 2021)
In the Macedonian medieval music and literary tradition, an intense reflection of the works of the Byzantine hymnographic genres had occurred through the Slavic translations, transcriptions and creative compilations in the so-called original Slavic hymnographic compositions. More precise structural research has shown that even the Slavic translations of the Byzantine hymnography reflected particular authorial interventions in the Byzantine form, as the translator was unable to fully adapt the original identical versification or the music (the melody) from the original into its translation, and sometimes there was a disruption of the original acrostic in the canonical songs. However, even the so-called original hymnographic works intended to eulogize and celebrate, were composed from a textual and structural perspective only in support of the Byzantine creative cliché, and they were supposed to reflect the general Christian theological views and cult impressions.